The service delivery of public stage bus services in urban and rural areas of Malaysia - Ponrahono, Zakiah; Bachok, Syahriah (IIUM Press, 2017)
The current bus systems adopted by many towns and rural areas in Malaysia, are not fully equipped to address the needs of the settlement forms, and socio-demographic and trip characteristics of the good urbanization process. These systems have portrayed a bad image on the overall connectivity and mobility in the urban or rural areas of Malaysia. Studies dwelling on the contemporary research of bus services quality in Malaysia have been limited, especially with regards to the comparison of urban and rural bus performances. Hence, this study focuses on assessing the level of service of bus services offered in selected urban and rural settlements in Malaysia. Five definitions of public transport level of services (LOS) according to Transportation Research Board are adopted. Assessment of the LOS has been conducted using both quantitative and qualitative methods of primary and secondary data capture. Three performance measures, namely fixed-route hour of service, fixed-route service frequency and passenger-load threshold were evaluated in determining the existence and extent of such disparities. Methods of on-board survey and adoption of Geographical Information System (GIS) /Global Positioning System (GPS) was deployed in the collection of primary data. The findings on the level of service (LOS) highlighted that the quality performance of the urban and rural bus service was still poor and lower than the tolerable threshold D. These also explicated some gaps and disparities in terms of (i) frequency, (ii) operation hour, (iii) bus speed, and (iv) passenger load threshold between the urban and rural bus operation systems. The recommendations put forward included the improvement of service facilities of dedicated bus lanes, high technology fleet, modern ticketing system, efficient information systems (arrival-departure time), locating the bus stops exactly on the alignment of the bus lanes, extended service hours into midnight and beyond, and adaptation of best practices in bus service system to ensure the future sustainability of urban and rural bus services in Malaysia.